Statistical quality control for the Six sigma green belt - Gupta, Bhisham C., 1942-; Walker, H. Fred, 1963- (ASQ Quality Press, 2007)
"This book is a desk reference and instructional aid for individuals involved with, or preparing for involvement with, Six Sigma project teams. As Six Sigma team members, Green Belts help select, collect data for, and assist with the interpretation of a variety of statistical or quantitative tools within the context of the Six Sigma methodology. The second in a four-book series geared specifically for these Green Belt activities, this book provides a thorough discussion of statistical quality control (SQC) tools. These tools are introduced and discussed from the perspective of application rather than theoretical development.